Cooperative effect of rapeseed oil-based polyol and egg shells on the structure and properties of rigid polyurethane foams. (October 2020) - Leszczyńska, Milena; Ryszkowska, Joanna; Szczepkowski, Leonard; Kurańska, Maria; Prociak, Aleksander; Leszczyński, Michał K.; Gloc, Michał; Antos-Bielska, Małgorzata; Mizera, Kamila
Abstract: Rigid polyurethane foams were manufactured using rapeseed oil-based polyol with hydroxyl number 270 mg KOH/g (10 wt% - 50 wt%) and ground egg shell waste as a natural filler (20 php) in a single-step synthesis procedure. The goal of the study was the investigation of the influence of renewable raw materials on the structure and physico-mechanical, thermal and biological properties of the final foams. The materials were analyzed using a variety of techniques involving: differential scanning calorimetry, thermogravimetric analysis, infrared spectroscopy, scanning electron microscopy and computer tomography as well as other methods in accordance to polish and international standards. The results clearly indicate that the modification of the polyurethane composition with the rapeseed oil-based polyol and egg shells leads to a beneficial influence on the foam structure. Depending on the renewable raw materials content, the modified materials exhibited similar or improved characteristics (compressive strength, surface bacteria adhesion, friability, water absorption, thermal stability, dimensional stability) in comparison to the reference foams obtained using only petrochemical substrates. Highlights: Polyurethane foams were prepared using rapeseed oil-based polyol and egg shell waste. The structure, physico-mechanical, thermal and biological properties were analyzed. Introduction of rapeseed polyol reduced friability and water absorption of the foams. Addition of natural polyol increased dimensional and thermal stability of the foams. Introduction of egg shell decreased the adhesion of bacteria to the foam surface.